The relationship between DNA fragmentation and the intensity of morphologically abnormal human spermatozoa - Mercedes González-Martínez; Pascual Sánchez-Martín; Carmen López-Fernández; Stephen D. Johnston; Jaime Gosálvez (Asian Pacific Journal of Reproduction)
Objective: To determine the relationship between teratozoospermia and sperm DNA fragmentation (SDF) in the human ejaculate. Methods: This retrospective study included 100 normozoospermic men as a control cohort (abnormal forms >14%), 210 patients with a high level of abnormal forms (≤4%) and 65 patients presenting with a moderate level of abnormal forms (>4% to ≤14%) based on the World Health Organization definitions. Sperm morphology was assessed using bright field microscopy. Sperm DNA fragmentation was assessed using the sperm chromatin dispersion assay. Non-parametric analyses were conducted to examine the relationship between abnormal sperm morphology and sperm DNA fragmentation; receiver operating characteristic (ROC) analyses were conducted to assess sensitivity and specificity of this relationship. Results: A correlation analysis revealed that the higher the proportion of abnormal spermatozoa in the ejaculate, the higher the level of SDF (Spearman's Rho = -0.230; P<0.001). Significant differences in the proportion of SDF were found when all cohorts were compared (P<0.001); these significant differences were also retained when the different cohorts were compared pairwise. ROC analysis showed a moderate but significant predictive value for SDF to differentiate patients with different levels of teratozoospemia. Conclusions: Although analysis of a more continuous range of values for teratozoospermia would help further clarify any causal relationship with SDF, there is clearly a synergistic or coincident affiliation between these variables that needs to be acknowledged by the clinician when interpreting the spermiogram.